Earning More and Getting Less - Tichenor, Veronica (Book collections on Project MUSE., 2005)
For nearly two decades the wage gap between men and women has remained virtually unchanged. Women continue to earn, on average, 80 cents for every dollar that men earn. Yet despite persistent discrimination in wages, studies are also beginning to show that a growing number of women are out-earning their husbands. Nationwide, nearly one-third of working women are the chief breadwinners in their families. The trend is particularly pronounced among the demographic of highly educated women. Does this increase in earnings, however, equate to a shift in power dynamics between husbands a.